Evaluacion de las condiciones de almacenamiento de las estacas de yuca para siembra - Mestra M., A. (International Center for Tropical Agriculture, 1990)
The effect of storing cassava planting material on root productivity was assessed and the influence of the length of the storage period on the sprouting of cassava cuttings was determined in trials carried out in the municipalities of Betulia and Corozal (Sucre, Colombia). Cassava var. Regional Venezolana was used and the following storage conditions were assessed: storage systems (under the shade of mango trees, direct sunlight, fresh roots), position (vertical, horizontal), and length (30, 60, and 90 days). Differences in sprouting were observed for the storage systems using the vertical position. The horizontal position was inadequate when cuttings were stored for 90 days. Sprouting of cuttings and fresh root yields were drastically reduced when cuttings came from lots that had not been defoliated by Erinnyis ello and had been kept for periods longer than 60 days. (CIAT)